2019
DOI: 10.1152/ajpheart.00257.2019
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic spinal cord neuromodulation obtunds dorsal root ganglion afferent neuronal transduction of the ischemic ventricle

Abstract: Aberrant afferent signaling drives adverse remodeling of the cardiac nervous system in ischemic heart disease. The study objective was to determine whether thoracic spinal dorsal column stimulation (SCS) modulates cardiac afferent sensory transduction of the ischemic ventricle. In anesthetized canines ( n = 16), extracellular activity generated by 62 dorsal root ganglia (DRG) soma (T1-T3), with verified myocardial ischemic (MI) sensitivity, were evaluated with and without 20-min preemptive SCS (T1-T3 spinal le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…In this study, DRGS prevented the reduction in ARI seen as a result of sympathetic hyperactivity during induced cardiac stress with programmed ventricular extrastimuli (S1S2 pacing). We and others have previously shown that ARI shortening occurs during increases in sympathetic discharge following cardiac stress (Vaseghi et al, 2013;Howard-Quijano et al, 2017a,b;Omura et al, 2021), and neuromodulation can block the cardiospinal neural reflex and prevent exaggerated sympathetic output to the heart (Salavatian et al, 2019). Our results show that DRGS reduced the cardiac sympathetic output via controlling the afferent arm of the cardio-neural reflex.…”
Section: Dorsal Root Ganglion Stimulation Modulation Of Cardiac Sympathetic Activity and Ventricular Excitabilitysupporting
confidence: 65%
“…In this study, DRGS prevented the reduction in ARI seen as a result of sympathetic hyperactivity during induced cardiac stress with programmed ventricular extrastimuli (S1S2 pacing). We and others have previously shown that ARI shortening occurs during increases in sympathetic discharge following cardiac stress (Vaseghi et al, 2013;Howard-Quijano et al, 2017a,b;Omura et al, 2021), and neuromodulation can block the cardiospinal neural reflex and prevent exaggerated sympathetic output to the heart (Salavatian et al, 2019). Our results show that DRGS reduced the cardiac sympathetic output via controlling the afferent arm of the cardio-neural reflex.…”
Section: Dorsal Root Ganglion Stimulation Modulation Of Cardiac Sympathetic Activity and Ventricular Excitabilitysupporting
confidence: 65%
“…Previous studies have shown that SCS significantly ameliorates myocardial ischemia and ventricular arrhythmias during ischemia and reperfusion (4,22). SCS significantly inhibits the abnormal activity of neurons in the dorsal horn at the T1-4 level (5). In this study, we confirmed that the pre-activation of glutamatergic neurons in the T1 dorsal horn inhibited ventricular arrhythmias during ischemia-reperfusion, suggesting that glutamatergic neurons played an important role in the protective mechanisms of SCS.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have reported that epidural anesthesia or spinal cord stimulation (SCS) reduces sympathetic excitation and malignant ventricular arrhythmias (4). SCS modulates afferent nervous signals (5), sympathetic neurotransmitter release (6,7), and autonomic dysregulation (4). Multiple interactions among neurons in the thoracic spinal cord may be involved in cardiac sympathetic overactivation (8).…”
Section: Introductionmentioning
confidence: 99%
“…As with many other neuromodulatory therapies, spinal cord stimulation (SCS) was initially developed to treat angina pectoris [143,144]. Though not completely understood, local stimulation of the spinal cord affects various central and local neural circuits, which collectively impede the process of arrhythmogenesis [145][146][147][148][149][150][151][152][153]. For instance, SCS impedes the ability of afferent cardiac nerves in transferring their signal to second-order spinal cord neurons, thereby hampering the initiation of a sympathetic reflex and the development of sympathetically driven remodeling processes that are induced by myocardial ischemia [146,147].…”
Section: Spinal Cord Stimulationmentioning
confidence: 99%
“…Though not completely understood, local stimulation of the spinal cord affects various central and local neural circuits, which collectively impede the process of arrhythmogenesis [145][146][147][148][149][150][151][152][153]. For instance, SCS impedes the ability of afferent cardiac nerves in transferring their signal to second-order spinal cord neurons, thereby hampering the initiation of a sympathetic reflex and the development of sympathetically driven remodeling processes that are induced by myocardial ischemia [146,147]. In addition, SCS stabilizes the ICNS and decreases left stellate ganglion activity, all of which could contribute to its antiarrhythmic effects [148,149,154].…”
Section: Spinal Cord Stimulationmentioning
confidence: 99%